Efektivitas Simulasi PhET Pada Pembelajaran IPA SMP Materi Konsep Listrik - Murwanto Setyo Nugroho; Budi Murtiyasa; Masduki (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study evaluates the effectiveness of using PhET (Physics Education Technology) simulations in enhancing critical thinking skills and learning outcomes of students on the topic of electricity at the junior high school level. Employing a quantitative approach and experimental design, the study involved 60 ninth-grade students from SMP Asy-Syifa Sukoharjo Boarding School, divided into control and experimental groups. Data were collected using validated and reliable questionnaires to measure critical thinking skills and students' learning outcomes. The data analysis revealed that the use of PhET simulations significantly improved critical thinking skills (p=0.008) and learning outcomes (p<0.001). Students in the experimental group demonstrated a higher average improvement in learning outcomes compared to the control group, with consistently enhanced conceptual understanding of electricity. These findings suggest that PhET simulations are an effective interactive learning tool for fostering conceptual comprehension and developing critical thinking skills. Integrating PhET as a digital learning medium can serve as an innovation to improve the quality of science education in the technological era.